Designing development processes related to system of systems using a modeling framework. Issue 6 (19th September 2019) - Shaked, Avi; Reich, Yoram
Abstract: As manmade systems become increasingly complex and evolve into Systems of Systems of various kinds, a multitude of tasks needs to be performed in coordination throughout their development. In this paper, we briefly introduce a new modeling framework that was designed following systems engineering principles and based on extensive research of development efforts characteristics. We focus on the framework's ability to support the design of development processes while addressing Systems of Systems‐related challenges. We then describe a case study of using this framework to introduce a new capability into a large enterprise, which specializes in systems and System of Systems development. The example demonstrates the utility of using this framework for planning complex development efforts as well as improving the coordination of multiple development efforts in System of Systems development scenarios.